Across the Tropical Pacific Ocean: Reflections on the Future of Kanaky-New Caledonia - Florence Boulard; Marine Lechene; Lola Kamblock (eTropic: electronic journal of studies in the tropics)
Imagination can be found in a range of human activities and the concept of envisioning the future has been a topic of discussion for centuries (Casey, 2000; Fuentes, 2017; Pelizzo, 2024;). Contemporary discussions on forecasting the future can often relate to climate change and geopolitical instability, as their profound impacts effect how societies must adapt. This paper draws attention to the imagined future of the often-overlooked Franco-Melanesian archipelago of Kanaky-New Caledonia in the South Pacific. As the local population faces growing uncertainties about their future, particularly since the riots of May 2024, it is timely to engage in such reflection. This study focuses on the narratives of the authors, three women from Kanaky-New Caledonia, who have migrated to Australia. As observers from across the ocean, we reflect on the challenges and possible futures of our island home; a place that remains deeply connected to our sense of identity. Here we draw from our experiences as women born across three different decades: the 1980s, 1990s, and 2000s.  By sharing our voices, this paper aims to contribute to the broader discussions about the future of Kanaky-New Caledonia.